CLPS: context-based location privacy scheme for VANETs. (2018) - Khacheba, Ines; Yagoubi, Mohamed B.; Lagraa, Nasreddine; Lakas, Abderrahmane
Location privacy preservation is considered as a challenge for deploying vehicular ad hoc networks (VANETs). In fact, the continuous periodical broadcast of spatiotemporal information in beacons allows a global passive adversary (GPA) to link pseudonyms and reconstruct vehicle traces. Consequently, it is imperative that a vehicle selects the right context to change pseudonym to confuse the adversary and ensure pseudonyms unlinkability. In this paper, we propose a context-based location privacy scheme (CLPS) that makes the following contributions: i) a pseudonym changing strategy that allows a vehicle to change pseudonyms based on its context; ii) a linkability threat, called cheating attack that negatively affects the proposed pseudonym changing strategy. A cheating detection mechanism is developed to allow a vehicle to detect misbehaving vehicles that launch the cheating attack, and assess the success of the pseudonym change. Finally, we evaluate CLPS against GPA by simulations using privacy extension, PREXT, in Veins, and we compare it against different existing privacy schemes.